CYTOKINES, CHEMOKINES AND GROWTH FACTORS ASSOCIATED WITH CHRONIC VIRAL HEPATITIS C - Natalia A. Arsentieva; Oleg K. Batsunov; Natalia E. Lyubimova; Valentina V. Basina; Elena V. Esaulenko; Areg A. Totolian (Медицинская иммунология, 2019)
Chronic hepatitis C (CHC) represents a significant public health concern. In the majority of cases, the infection progresses to a chronic form, which is characterised by the development of fibrosis and cirrhosis of the liver. A plethora of cytokines and chemokines are generated as a consequence of inflammatory processes within the liver. These can exert a dual effect, both protective and damaging, particularly in relation to the death of hepatocytes and the progression of liver fibrosis. Furthermore, a number of growth factors have been identified as playing a role in the pathogenesis of CHC. The objective of the study was a comprehensive evaluation of a wide range of cytokines, chemokines and growth factors in the blood plasma of patients with CHC at varying stages of liver fibrosis. The study cohort comprised 63 patients diagnosed with CHC, who were divided into three groups according to the stage of liver fibrosis. The control group comprised healthy individuals (n=32). Concentrations of the following cytokines were determined in plasma: Interleukins and some cytokines (IL-1α, IL-1β, IL-1RA, IL-2, IL-4, IL-5, IL-6, IL-7, IL-9, IL-10, IL-12 (p40), IL-12 (p70), IL-13, IL-15, IL-17A, IL-17-E/IL-25, IL-17F, IL-18, IL-27, IFNα, IFNγ, TNFα, TNFβ); chemokines (CCL2/MCP-1, CCL3/MIP-1α, CCL4/MIP-1β, CCL7/MCP-3, CCL11/Eotaxin, CCL22/MDC, CXCL1/GROα, CXCL8/IL-8, CXCL9/MIG, CXCL10/IP-10, CX3CL1/Fractalkine) and growth factors (EGF, FGF-2, Flt-3L, G-CSF, M-CSF, PDGF-AA, PDGF-AB/BB, TGFα, VEGF-A) by multiplex analysis based on xMAP technology. Nonparametric statistics methods were used for statistical analysis. As a result of the study, increased concentrations of cytokines IL-12 (p40), IL-15, IL-17E/IL-25, IL-27, IFNγ, TNFα, chemokines CXCL9/MIG and CXCL-10/IP-10 and growth factors FGF-2 and M-CSF were found at all stages of liver fibrosis. Elevated concentrations of cytokines IL-1α, IL-1β, IL-2, IL-6, IL-9, IL-10, IL-17F, IFNα, TNFβ, chemokines CCL2/MCP-1, CCL11/Eotaxin, CCL22/MDC and growth factors G-CSF, TGFα, Flt-3L were found in severe liver fibrosis/cirrhosis. Correlation analysis revealed a relationship of high significance between the severity of liver fibrosis and the content of cytokines IL-6, IFNγ, TNFα, IL-7, chemokines CCL2/MCP-1, CCL11/Eotaxin, CXCL9/MIG, CXCL10/IP-10, CXCL1/GROα, growth factors TGFα, PDGF-AA, PDGF-AB/BB. Thus, a certain profile of cytokines characteristic for CHC was revealed, cytokines, chemokines and growth factors significant for liver fibrosis in CHC were found.